Cool features of steel 70H5VMF from austenitizing temperature in bulk graphite - Заблоцкий, Владимир Кириллович; Шимко, Владимир Игоревич; Шимко, Алексей Игоревич (Eastern-European Journal of Enterprise Technologies, 2012)
The processes occurring during continuous cooling steel 70H5VMF in bulk graphite are studied It is established that the diagram isothermal transformation of austenite is a genetic memory or the genetic steel code to study the transformations occurring during cooling at different rates